Combining digital adherence technology and therapeutic drug monitoring for personalised tuberculosis care. Issue 6 (8th December 2022) - Ghimire, Samiksha; Iskandar, Deni; van der Borg-Boekhout, Roelina; Zenina, Marina; Bolhuis, Mathieu S.; Kerstjens, Huib A.M.; van Rossum, Marieke; Touw, Daan J.; Zijp, Tanja R.; van Boven, Job F.M.; Akkerman, Onno W.
Tuberculosis (TB) is the world's leading cause of infectious disease-related mortality, apart from COVID-19 presently [1]. Standard TB treatment for drug-susceptible (DS) TB takes 6–9 months and requires daily intake of multiple medications [1]. Notably, proper treatment adherence is essential for successful treatment outcome [1, 2]. To improve adherence, counselling and education are important. Digital adherence technology in combination with therapeutic drug monitoring could aid in supporting adherence and personalising dosing while at the same time supporting patients to carry out TB medication related tasks independently https://bit.ly/3gh1A1c